2005
DOI: 10.1093/geront/45.suppl_1.27
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Three Methods of Measuring Dementia-Specific Quality of Life: Perspectives of Residents, Staff, and Observers

Abstract: Each perspective is relatively independent and somewhat unique. Measures that focus on specific aspects of quality of life may be more appropriate to use with assisted living residents than with residents of special care facilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
143
2
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(154 citation statements)
references
References 14 publications
6
143
2
3
Order By: Relevance
“…The QOL-AD associated most significantly with the Hamilton Depression Rating Scale, Neuropsychiatric Inventory, neuropsychological test that assesses various aspects of orientation, memory, language, praxis, attention, and executive function, and Rating of Awareness Deficits, even though they clear differ between studies 7,12,23 . QOL is weakly correlated with cognition, and in some studies behavioral and psychological disturbances are more strongly associated with QOL than cognition or functional limitations 4,12,23 . The patient's QOL version also revealed associated factors that explain higher variance percentages (48.3%) than the carerpatient QOL ratings (37.5%) 7 .…”
Section: Discussionmentioning
confidence: 96%
“…The QOL-AD associated most significantly with the Hamilton Depression Rating Scale, Neuropsychiatric Inventory, neuropsychological test that assesses various aspects of orientation, memory, language, praxis, attention, and executive function, and Rating of Awareness Deficits, even though they clear differ between studies 7,12,23 . QOL is weakly correlated with cognition, and in some studies behavioral and psychological disturbances are more strongly associated with QOL than cognition or functional limitations 4,12,23 . The patient's QOL version also revealed associated factors that explain higher variance percentages (48.3%) than the carerpatient QOL ratings (37.5%) 7 .…”
Section: Discussionmentioning
confidence: 96%
“…Particular techniques are required to meaningfully communicate and interact with patients with dementia. When health professionals learn the appropriate techniques for communication and interaction, staff wellbeing is enhanced along with the patient's quality of life [8] . For a considerable time, studies have indicated a need for improved dementia education and training for nurses and other health care staff in acute services.…”
Section: Staff Knowledge and Understanding Of Dementia Care In Acute mentioning
confidence: 99%
“…Previous studies of QOL of people with dementia have focused predominantly on individuals living in long-term care (Lyketsos et al, 2003) or assisted living facilities (Edelman, Fulton, Kuhn, & Chang, 2005) in urban or semi-urban areas. There is little published research involving non-institutionalized, community-dwelling persons with dementia in rural settings, and it is unknown whether the QOL of patients with dementia in a rural setting will resemble the QOL of patients in an urban environment.…”
Section: Definition Of Quality Of Lifementioning
confidence: 99%